PENGEMBANGAN APLIKASI BELAJARNGAJI BERBASIS ANDROID MENGGUNAKAN .NET MAUI - Choeriyah, Sahara Syarifatul; Syauqi Fanhas, Riezan; Anggraeni, Reni (LPPM Sekolah Tinggi Teknologi Cipasung, 2024)
The process of reciting the Koran is an activity that is often carried out by Muslims to read and practice the Al-Quran. The process of reciting the Koran and blind reading of the Koran is currently still lacking and is considered high so there must be changes or improvements in the process of learning to recite the Koran. So this research aims to develop an Android-based LearningNgaji application with the Extreme Programming development method using the .NET MAUI framework by applying the MVVM pattern. The result of this research is an Android-based BelajarNgaji application which includes a process page for managing user data, selecting a Koran recitation session, approving a Koran recitation session, and conducting a Koran recitation session, thus helping with problems in the Koran recitation process and making it easier for users to learn the Koran.